Shaping Artificial Intelligence Governance and Risk Management in the Public Sector: Regulatory Insights - Gandung Troy Sulistyantoro; Akhsanul Khaq; Md Zubair Kasem Khan; Al Amin; Abdullah-Al-Monzur Hussain (APPTHI, 2024)
As AI continues to transform public services by enhancing efficiency, transparency, and decision-making, it also brings forth significant challenges related to data privacy and misuse. This research explores the intersection of risk management and AI governance within Indonesia's public administration, by conceptualizing how Indonesia's legal frameworks, regulations, and policies should evolve to accommodate AI technologies responsibly. The research employs a conceptual approach to analyze existing laws, including the Personal Data Protection Act and the Information and Electronic Transactions Law, alongside international best practices. The findings emphasize the need for a clear and cohesive regulatory framework that governs AI usage, with a focus on data privacy, ethical AI use, and transparency. It is concluded that Indonesia must strengthen its data protection laws, address the shortage of AI professionals, and improve infrastructure to ensure the responsible implementation of AI in public administration.